PERANCANGAN LAYANAN SISTEM SELULAR PADA ADAPTIVE CDMA S-ALOHA DENGAN IGA - Hoga Saragih (Universitas Ahmad Dahlan, 2008)
Design of celluler system servicing with adaptive code-division multiple-access slotted-ALOHA (adaptive CDMA S-ALOHA) using improved Gaussian approximation (IGA) was analyzed. In this analysis, the algorithms set of change in the level of transmission speed for user based on the traffic condition occurs. The using of CDMA S-ALOHA channel access protocol is a mix of S-ALOHA and CDMA access methods in wireless communication systems. This method allows the user to access simultaneously, and the using of spectrum is efficient that it is advantages of CDMA S-ALOHA. Adaptive CDMA S-ALOHA method is a technique that can make adjustments based on the level of transmission speed of traffic conditions. As a result, the throughput of adaptive CDMA S-ALOHA based on IGA more accurate than based on Gaussian Approximation (GA).